Strukturalna miara rozwoju obiektów hierarchicznych - Strahl, Danuta (Structural Measure of Development of Hierarchical Objects, 2006)
The article presents a proposal of constructing a structural measure of development, taking into account the internal diversification of statistical hierarchical objects that include lower-tier objects. The structural measure of development has two versions. The first is based on the number of lower-tier objects, and the other one - on the lower-tier objects' potential. The measure was used to evaluate regional development of 25 countries of enlarged Europe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 11-20